Bursaphelenchus xylophilus detection and analysis system based on CRISPR – Cas12 - Wang, Xiang; Wang, Lai-Fa; Cao, Ye-Fan; Yuan, Yan-Zhi; Hu, Jian; Chen, Zu-Hai; Zhu, Fei; Wang, Xi-Zhuo (Frontiers in Plant Science, 2022)
Pine wilt disease is caused by the pine wood nematode (Bursaphelenchus xylophilus) and leads to wilting and death of pines. It is one of the most damaging diseases of pines worldwide. Therefore, accurate and rapid detection methods are of great importance for the control of B. xylophilus. Traditional detection methods have some problems, such as being time-consuming and requiring expensive instruments. In this study, we established an intelligent detection and analysis system for B. xylophilus that integrates field sampling, rapid detection, and intelligent control analysis. The process can be completed within 1 hour, from sample pretreatment and detection to data analysis. Loop-mediated isothermal amplification (LAMP) combined with a clustered regularly interspaced short palindromic repeats (CRISPR) method are used in this system, which we called the LAMP-CRISPR/Cas12a assay. Compared with the single LAMP method, the LAMP-CRISPR/Cas12a assay uses species-specific fluorescence cleavage to detect target amplicons. This process confirms the amplicon identity, thereby avoiding false-positive results from non-specific amplicons, and the large amounts of irrelevant background DNA do not interfere with the reaction. The LAMP-CRISPR/Cas12a assay was applied to 46 pine wood samples and the samples carrying B. xylophilus nematodes were successfully identified. To meet the needs of different environments, we designed three methods to interpret the data: 1) naked eye interpretation; 2) lateral flow biosensor assay; and 3) integrated molecular analysis system to standardize and intellectualize the detection process. Application of the B. xylophilus detection and analysis system will reduce the professional and technical requirements for the operating environment and operators and help to ensure the accuracy of the detection results, which is important in grass-root B. xylophilus detection institutions.